New Governance for Rural America Creating Intergovernmental Partnerships - Radin, Beryl A. (University Press of Kansas, 1996)
Throughout the 1990s public demand for a fundamental shift in the relationship between government and its citizens has intensified. In response, a "new governance" model has emerged, emphasizing decreased federal control in favor of intergovernmental collaboration and increased involvement of state, local, and private agencies. As the authors of this volume show, one of the best examples of "new governance" can be found in the National and State Rural Development Councils (NRDC and SRDC), created in 1990 as the result of President Bush's Rural Development Initiative and now called the Rural Development Partnership. This effort was part of a move within policymaking circles to redefine a rural America that was no longer synonymous with family farming and that required innovative new solutions for economic revival. By 1994 twenty-nine states had created and ten other states were in the process of forming such councils. In this first detailed analysis of the NRDC and SRDCs, the authors examine the successes and failures of the original eight councils in Kansas, Maine, Mississippi, Oregon, South Carolina, South Dakota, Texas, and Washington; as well as eight other councils subsequently created in Iowa, New Mexico, North Carolina, Vermont, New York, North Dakota, Utah, and Wyoming. Combining empirical analysis with current theories about networks and inter-organizational relations, this volume should appeal to academics and practitioners interested in rural development policy, public administration, public policy and management, and intergovernmental relations. Open access edition funded by the National Endowment for Humanities and the Andrew W. Mellon Foundation Humanities Open Book Program.